2015
DOI: 10.4238/2015.may.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin-1β -511C/T promoter polymorphism with COPD risk: a meta-analysis

Abstract: ABSTRACT. Studies examining the role of interleukin (IL)-1β -511C/ T promoter polymorphism in the pathogenesis of chronic obstructive pulmonary disease (COPD) have shown inconsistent results. This metaanalysis was performed to assess the association between the IL-1β -511C/T promoter polymorphism and COPD susceptibility. Published case-control, cross-sectional, and cohort studies from Pubmed, Embase, and China National Knowledge Infrastructure databases were retrieved. Data were extracted and pooled odds ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In our report, a 72-year-old male, a chronic smoker serotonin and histamine show a high levels in COPD patients [14,15].…”
Section: Case Reportmentioning
confidence: 45%
“…In our report, a 72-year-old male, a chronic smoker serotonin and histamine show a high levels in COPD patients [14,15].…”
Section: Case Reportmentioning
confidence: 45%
“…These meta-analyses included a mean of 6 studies (range 1–15) and 5587 participants (range 220–100777). Except 48 statistically nonsignificant associations, 9 significant associations were identified in the stratified analysis by ethnicity [ 8 , 36 , 42 , 54 , 55 , 59 , 65 , 70 ]. Only 4 associations met the following criteria for further assessment: genetic model must be an allelic model, and significant association was congruously confirmed across studies.…”
Section: Resultsmentioning
confidence: 96%
“…A meta-analysis of available data presents the precise estimation of the effects of the polymorphisms. Previous meta-analyses showed that IL1β polymorphisms affect the risk of various clinical conditions and cancers ( 46 - 48 ). However, to this date, no meta-analysis study has reported a precise correlation between IL1β polymorphisms and the risk of gestational disorders.…”
Section: Discussionmentioning
confidence: 99%